Turning Teaching Inside Out : A Pedagogy of Transformation for Community-Based Education - Davis, Simone Weil.; Roswell, Barbara Sherr; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2013)
Using the successful Inside-Out program, in which incarcerated and non-incarcerated college students are taught in the same classroom, this book explores the practice of community-based learning, including the voices of teachers and participants, and offers a model for courses, student life programs, and faculty training.
Keywords: Science; Science; Science, general